Emotional And Social Intelligence Of The Employees Of It Companies In Chennai (Journal of Pharmaceutical Negative Results, 2023)
Emotional Intelligence (EI) and Social Intelligence (SI) serves as the essential factors for achieving the Organizational Goals. EI refers to the understanding and managing the employees’ emotions intellectually. SI refers to the responding towards the employees’behaviour according to the right situation. This research mainly concerned with the EI Factors namely,Resilience, Motivation, Self-Awareness, Conscientiousness, Intuitiveness, Influence and Interpersonal Sensitivityand SI Factors such asConsciousness, Insight, Social Awareness and Behavioural Sideby targeting towards ninety Associate Programmer Analysts and thirty Project Managers in Information Technologies Companies in Chennai. This Research Article highlights the influence ofpersonalvariables on EI as well as SI Factors, which identifies that Gender and Designations impacts the EI and SI of Associate Programmer Analysts and Project Managers. Whereas, Experience does not impact the EI and SI of Associate Programmer Analysts and Project Managers. Income levels of the Associate Programme Analysts directly impacts the SI. This study further highlights that the ranking preferences given by the Associate Programmer Analysts and Project Managers towards the EI and SI Factors are found to be equally effective.